62 THE EFFECTS OF DANAZOL ON LIPOPROTEIN PROFILES IN POSTMENOPAUSAL PATIENTS. (1st January 2006) - Morris, D.; Files, J.
Abstract : Danazol is a synthetic heterocyclic steroid derived from 17 alpha-ethynyl testosterone. The initial application of danazol was the symptomatic treatment of endometriosis. Subsequent clinical applications include the treatment of cystic disease of the breast, excessive menstrual blood loss, and immune-mediated thrombocytopenia refractory to standard therapy. Danazol is often poorly tolerated with side effects, including weight gain, muscle cramps, and occasional irreversible virilization. Additional studies have shown that patients taking danazol have demonstrated increased levels of prealbumin, haptoglobin, antithrombin III, and other plasma proteins synthesized by the liver. Alterations in lipoprotein profiles have also been reported, including elevations in low-density lipoprotein levels (LDL-c) and decreased levels of high-density lipoproteins (HDL-c). The subtype of HDL-c most affected by patients undergoing treatment has been shown in clinical studies to be HDL-2. The mechanism of action by which danazol results in these effects has not been well established due to its complex pharmacology. Danazol's pharmacological actions include the inhibition of both gonadotropin-releasing hormone and multiple enzymes of adrenal and gonadal steroidogenesis. Danazol also has mild androgenic steroid properties that not only contribute to physically apparent side effects but also to chemical and hormonal changes, which can be monitored by laboratory analysis. Some initial studies on these changes in premenopausal woman led investigators to postulate that the suppression of the pituitary-ovarian axis and decreases in estrogen levels were responsible for the changes in lipid profiles. This theory is not supported by studies involving lipoprotein levels in patients taking other inhibitors of gonadotropin-releasing hormone. However, examination of lipid profile alterations in patients taking androgenic steroids is similar to patients on danazol, including increases in LDL-c and decreases in HDL-c most notably HDL-2. A review of a small group of postmenopausal patients taking danazol was performed. Analysis of lipoprotein profiles demonstrated a significant change in LDL-c and HDL-c that was similar to those demonstrated in patients taking androgenic steroids. Clinical consideration of cardiovascular risk should be given to patients taking danazol with monitoring of lipoprotein profiles during treatment.